2016
DOI: 10.1038/nrendo.2016.171
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Metabolic effects of smoking cessation

Abstract: On page 302 of the above article, VLDL in Figure 2 was incorrectly labelled as VDL. This has been corrected online. C O R R E C T I O NNATURE REVIEWS | ENDOCRINOLOGY www.nature.com/nrendo © 2 0 1 6 M a c m i l l a n P u b l i s h e r s L i m i t e d , p a r t o f S p r i n g e r N a t u r e . A l l r i g h t s r e s e r v e d .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…Recent evidence indicates that the risk of developing type 2 diabetes is 30–40% higher in smokers that nonsmokers [ 9 ]. Passive (second-hand) smoking has also been linked with negative health consequences such as low-birth rate in offspring of mothers exposed to second-hand smoke, sudden infant death syndrome, and type 2 diabetes mellitus [ 28 ].…”
Section: Health Effects Of Cigarette (Tobacco) Smokingmentioning
confidence: 99%
“…Recent evidence indicates that the risk of developing type 2 diabetes is 30–40% higher in smokers that nonsmokers [ 9 ]. Passive (second-hand) smoking has also been linked with negative health consequences such as low-birth rate in offspring of mothers exposed to second-hand smoke, sudden infant death syndrome, and type 2 diabetes mellitus [ 28 ].…”
Section: Health Effects Of Cigarette (Tobacco) Smokingmentioning
confidence: 99%
“…29) Various toxic substances, such as nicotine, carbon monoxide and oxidizing gas from cigarette, cause abnormalities in lipoprotein metabolism, endothelial cell dysfunction and insulin resistance, which increase the risk of MetS. 30) 31) 32) 33) 34) Nicotine stimulates the release of adrenaline, which increases blood pressure and heart rate. 35) It has been suggested that nicotine induces lipolysis in adipose tissue, increases triglyceride, and low-density lipoprotein (LDL) cholesterol, and decrease HDL cholesterol in the blood.…”
Section: Smoking Cessationmentioning
confidence: 99%
“… 34) The risk of MetS due to smoking increases in proportion to the amount of smoking. 33) Smoking cessation reduces the risk of developing MetS, cardiovascular disease and mortality, 31) 38) 39) so smoking cessation should be emphasized. However, for some time after quitting smoking, weight gain may occur, so lifestyle modification should be implemented more thoroughly after smoking cessation.…”
Section: Smoking Cessationmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking cessation alleviates diseases caused by smoking (1,2), and the reduction of oxidative damage is one expected benefit (3). Past intervention studies reported that smoking cessation yielded reduced levels of urinary 8-hydroxy-2′-deoxyguanosine (8-OHdG) and 8-iso-prostaglandin F2α (8-isoprostane) (3,4).…”
Section: Introductionmentioning
confidence: 99%